CO2 Abatement and Fuel Mix in German Electric Power Generation: Is the Ecological Electricity Tax Ecologically Effective? - Tauchmann, Harald (Energy & Environment, 2005)
This paper analyzes the effect of a potential carbon tax on inter-fuel substitution in the electric power sector in Germany. By analyzing firm level panel data (1980-1998), we show that the fuel mix as used by power plants is price inelastic. That means that differential fuel taxes, e.g. a carbon tax, will not induce inter-fuel substitution towards less carbon intensive fuels. This in turn means that the recent introduction in Germany of an electricity tax cannot be judged less effective than the hypothetical introduction of a carbon tax with respect to power related CO2 emissions. It is likely, however, that in the course of the deregulation of the German power sector a carbon tax will become significantly more effective than an electricity tax.
WiSo-Import:2015-03-26:4671
Keywords: CO; Ecological effectiveness; Fuel mix; German ecological tax reform